A cross-sectional study of awareness and practices regarding thalassemia among parents of thalassemic children - Jain, Ankur (J Family Med Prim Care, 2020)
BACKGROUND: This cross-sectional study was carried out in thalassemia ward of Rajindra Hospital, Patiala, among the parents of thalassemic children to determine awareness about side effects and complications of blood transfusion therapy, other treatment options, nature of disease, and food practices of transfusion-dependent patients. The study was carried out using a predesigned questionnaire and 118 parents participated in the study. About 50.84% patients belonged to the Sikh community, 45.76% patients practiced Hindu religion, and only 3.38% of the patients were Muslim. This study shows that 87.29% parents do not know how the disease is spread. About 55.93% have no knowledge about iron-containing food should not be included in the diet of transfusion-dependent patients. About 86.44% parents believed they had no role in transmission of the disease to their child, 79.66% parents do not understand the importance of screening before marriage, and 95.76% parents do not know about alternative treatment options. This study wants to shine light about the inadequate and superficial knowledge of thalassemia among general public and how awareness of the disease will bring down the incidence rates. AIMS: The main objective of the study is to determine the degree of awareness of the disease, their knowledge of complications of blood transfusion therapy, and other treatment options among the parents of the children with thalassemia who are currently on blood transfusion therapy. SUBJECTS AND METHODS: This cross-sectional study was conducted in thalassemia ward of Rajindra Hospital, Patiala from June 2018 to November 2018. After informed verbal consent was ensured, parents of the patients were interviewed using a questionnaire as the patients received blood transfusion. Questions include prevention, progression, cause, and spread, of the disease. The questions also include side effects and complications of blood transfusion therapy and other treatment options available. STATISTICS USED: Continuous variables were summarized as mean and standard deviation and categorical variables as proportion (%). Percentage and frequency was used wherever applicable. RESULTS: Parents of about 118 patients were interviewed out of which 74.57% parents were illiterate and only 25.42% were literate. About 50.84% of the patients were Sikh, 45.76% were Hindu, and only 3.38% patients were Muslims. About 71.19% of the parents had no knowledge about the prevention of the disease, and 87.29% of the parents did not know mechanism of spread. Despite having transfusion-dependent children, only 44.07% of the parents restricted iron-containing food from the diet of their children. About 72.05% of the patients have inadequate information about risk of hepatitis B, hepatitis C, and HIV due to blood transfusions and only 21.29% of the patients understand the importance of hepatitis B vaccine. CONCLUSION: Awareness among both literate and illiterate parents was inadequate and sensitization among general public and parents of thalasemmic children should be initiated.